The mitochondrial pathway is involved in sodium fluoride (NaF)-induced renal apoptosis in mice. Issue 5 (11th July 2018) - Wei, Qin; Luo, Qin; Liu, Huan; Chen, Linlin; Cui, Hengmin; Fang, Jing; Zuo, Zhicai; Deng, Junliang; Li, Yinglun; Wang, Xun; Zhao, Ling
Abstract : The objective of the present study was to explore the molecular mechanism of apoptosis induced by sodium fluoride (NaF) in the mouse kidney by using the methods of flow cytometry, quantitative real-time polymerase chain reaction (qRT-PCR), western blotting, and experimental pathology. Abstract : The objective of the present study was to explore the molecular mechanism of apoptosis induced by sodium fluoride (NaF) in the mouse kidney by using the methods of flow cytometry, quantitative real-time polymerase chain reaction (qRT-PCR), western blotting, and experimental pathology. 240 four-week-old ICR mice were randomly divided into 4 groups and exposed to different concentrations of NaF (0 mg kg −1, 12 mg kg −1, 24 mg kg −1 and 48 mg kg −1 ) for a period of 42 days. The results demonstrated that NaF increased cell apoptosis and the depolarization of the mitochondrial membrane potential (MMP), and that the mitochondrial pathway was involved in NaF-induced apoptosis. Alteration of the mitochondrial pathway was characterized by significantly increasing mRNA and protein expression levels of cytosolic cytochrome c (Cyt c), the second mitochondrial activator of caspases/direct inhibitors of the apoptosis binding protein with low pI (Smac/Diablo), the serine protease high-temperature-requirement protein A2/Omi (HtrA2/Omi), the apoptosis inducing factor (AIF), endonuclease G (Endo G), cleaved-cysteine aspartate specific protease-9 (cleaved-caspase-9), cleaved-cysteine aspartate specific protease-3 (cleaved-caspase-3), Bcl-2 antagonist killer (Bak), Bcl-2 associated X protein (Bax), Bcl-2 interacting mediator of cell death (Bim), cleaved-poly-ADP-ribose polymerase (cleaved-PARP), p-p53, and decreasing mRNA and protein expression levels of B-cell lymphoma-2 (Bcl-2), Bcl-extra large (Bcl-xL), and X chromosome-linked inhibitors of apoptosis proteins (XIAPs). To our knowledge, the mitochondrial pathway is reported for the first time in NaF-induced apoptosis of the human or animal kidney. Also, this study provides novel insights for further studying fluoride-induced nephrotoxicity.